SISTEM INFORMASI KEAMANAN BRANKAS DENGAN MITROKONTROLER ATMEGA 16 - Hafdiarsya Saiyar; Mohammad Noviansyah (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Security has become a necessity that is needed by everyone. In terms of money storage, the authors make a information security system in a safe with an ATmega 16 mitrocontroller. This system consists of two important parts, namely a mitrocontroller and mobile phone as a transfer medium. data and hardware systems consist of atmega 16 mitrocontrollers, LCDs, solenoids, keypads and sim800. This security system aims to improve security of safes. This will provide convenience and benefits for the community and companies that use it as a safe deposit box with passwords and SMS (short message service). The workings of this security system are as follows when the password that we enter is correct, then the safe door will open and if the password is incorrect, the safe owner will get an SMS (short message service) from the security system in the safe.